Effects of Posture Correction on Chest Expansion with patient with Forward Head Posture - Mohtishim Ahmed, Wajeeha, Halima Shoukat, Komal Tehzaib, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Poor posture and sedentary lifestyle cause Forward Head Posture (FHP). Although Posture Correction Band (PCB) is used quite often to correct FHP, yet it is not exactly known that the PCB influenced the chest expansion in population with FHP. Aim: To find out the effects of PCB on chest expansion in population with FHP. Methodology: Randomized Control trial was conducted on forty-two subjects with forward head posture. Subjects were divided in two groups. G1 was educated as per McKenzie exercise principle. G2 wore postural correction band. Results: Data was entered and analyzed by SPSS version 25. The mean age in Group 1 was 27.09±6.33 and in Group 2 was 29.5±5.34 in terms of outcome measures of chest expansion. The chest expansion was significant in group B with mean clinical difference as 0.22±0.05, 0.39±0.08 and 0.21±0.09 at axillary, 4th intercostal and xiphisternum level respectively. Conclusion: The study concluded that there are significant effects of wearing PCB on chest expansion in terms of mean clinical significance and statistical significance. Keywords: Chest Expansion, Forward Head Posture, Posture Correction Band